Letter (copy) : Goods for Spain - Citrine, Walter, 1887-1983
029-0179-001 WMC/EAB/AC/599 International 10th April, 1937. Mr. J. Thompson, Co-operative Wholesale Society Ltd., Export Dept., 1, Balloon Street, MANCHESTER, 4. Dear Mr. Thompson, GOODS FOR SPAIN. In confirmation of our telephone conversation yesterday, you will proceed with the arrangements to ship by the "Backworth", which is due to leave Immingham on 15th April. The goods are to be cossigned to: Dirección de Abastecimientos, BILBAO. Yours sincerely, General Secretary. 292/946/29/179